PENGARUH PENDAPATAN ASLI DAERAH, SISA LEBIH PEMBIAYAAN ANGGARAN, DANA ALOKASI UMUM DAN DANA BAGI HASIL TERHADAP BELANJA MODAL DI PROVINSI ACEH - Dhaniel Akbar; Murtala Murtala; Asnawi Asnawi (Jurnal Ekonomi Regional Unimal, 2022)
This study  analyzed  the effect of  local revenue, excess budget financing, general allocation funds, and revenue-sharing funds in regencies/cities in Aceh province on capital expenditures in regencies/cities in Aceh province. This study used quantitative data with a panel data approach, consisting of time-series data for five years from2015  to  2019  and  cross-sectional  data  from  23  regencies/cities,  as  well  as  115observations of data. The analytical method used was panel data regression with the selected Fixed Effect Model. The results partially indicated that local revenue did not influence capital expenditures in 23 regencies/cities in Aceh province, the remaining budget for financing and profit-sharing funds have a positive and significant effect on capital expenditures for regencies/cities in Aceh province, while general allocation funds positively and  significantly influenced  Capital  Expenditures  in  23 regencies/cities  in  Aceh  province.  Simultaneously,  local  revenue,  the  remaining budget for financing, General allocation funds, and profit-sharing funds have a positive and significant impact on capital expenditures in 23 districts/cities of Aceh Province.